Exploring Students’ Algebraic Reasoning on Quadratic Equations: Implications for School-Based Assessment - Mukuka, Angel; Balimuttajjo, Sudi; Mutarutinya, Védaste (International Conference to Review Research in Science, Technology, and Mathematics Education, 2020)
The first encounter with abstract mathematical reasoning impedes the understanding of algebra for most students at lower secondary education levels, which continues to upper levels and beyond. A descriptive survey research involving 300 grade 11 students of ages 14 to 20 clustered into low, moderate, and high academic performance was conducted. Written responses were collected using a Mathematical Reasoning Test, regarding students’ argumentation modes for justifying an algebraic conjecture and assessment of suggested solutions for a given quadratic equation. Chi-square test revealed no significant relationship between students’ modes of justification and the type of school they came from, c2(4) = .50, p =.97. However, the majority exhibited limited forms of understanding and comprehension of quadratic equations. There is a serious need for more attention to students’ algebraic reasoning in school-based assessment of mathematical learning.
Keywords: Algebraic reasoning; School-based assessment; Quadratic equations